1991
DOI: 10.1007/bf01297142
|View full text |Cite
|
Sign up to set email alerts
|

Flexible sigmoidoscopy may be ineffective for secondary prevention of colorectal cancer in asymptomatic, average-risk men

Abstract: Asymptomatic men (N = 114) 50 years of age or older had screening for colorectal neoplasia with flexible sigmoidoscopy followed by colonoscopy regardless of the sigmoidoscopic result. Our study objective was to determine the prevalence of patients having isolated adenomatous polyps in a proximal colonic segment in the absence of a distal index neoplasm within reach of the sigmoidoscope. Through the combined use of sigmoidoscopy and colonoscopy, adenomatous polyps were detected in 47 of 114 individuals (41%). A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0
1

Year Published

1994
1994
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(40 citation statements)
references
References 28 publications
1
38
0
1
Order By: Relevance
“…Rex et al (13) reported that 15% of asymptomatic men and 7% of women aged 60 yr or older had advanced colorectal neoplasms. Similar percentages had been found in small clinical series and autopsy studies (11,12,14,(40)(41)(42). We found a linear association between age and the prevalence of advanced colonic neoplasia.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Rex et al (13) reported that 15% of asymptomatic men and 7% of women aged 60 yr or older had advanced colorectal neoplasms. Similar percentages had been found in small clinical series and autopsy studies (11,12,14,(40)(41)(42). We found a linear association between age and the prevalence of advanced colonic neoplasia.…”
Section: Discussionsupporting
confidence: 74%
“…Screening with full colonoscopy as a primary procedure has been limited to a few small series (10)(11)(12)(13)(14)(15)(16), and results have not been focused in advanced adenomas. Two large colonoscopic series recently published (17,18) have assessed the proportion of advanced proximal adenomas in average risk adults.…”
Section: Introductionmentioning
confidence: 99%
“…[22][23][24][25][26][27][28][29][30][31][32][33][34][35] Only studies wherein colonoscopy is offered as a primary screening procedure can appropriately address this issue. Currently, such data that are available derive from 3 studies that comprise relatively few cases [36][37][38] and two large studies carried out in the United States. 18,19 These large studies from the United States assess the usefulness of applying endoscopic and histopathologic findings in the distal colon to predict the likelihood of finding advanced proximal neoplasms.…”
Section: Introductionmentioning
confidence: 99%
“…there were already several cross sectional studies of colonoscopy in asymptomatic volunteers underway [2][3][4][5] , and the results were published in 1990 and 1991 [2][3][4][5] . These 4 studies eventually totaled just over 1000 patients [2][3][4][5][6] , and demonstrated that the prevalence of adenomas in asymptomatic persons is substantial, age-related, and higher in males [2][3][4][5][6] .…”
Section: Introduction and Historical Perspective On Screening Colonosmentioning
confidence: 99%
“…These 4 studies eventually totaled just over 1000 patients [2][3][4][5][6] , and demonstrated that the prevalence of adenomas in asymptomatic persons is substantial, age-related, and higher in males [2][3][4][5][6] .…”
Section: Introduction and Historical Perspective On Screening Colonosmentioning
confidence: 99%